GREEN LOGISTICSKA- THE PRINCIPLE OF SUSTAINABLE DEVELOPMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article is devoted to the issue of "green" logistics in the market of Uzbekistan. National enterprises are interested in" green " technologies in order to reduce costs, extract benefits and minimize the impact of logistics systems on the environment as a whole. The main focus is on technologies that are not mandatory for regulation, but benefit the environment and companies that are focused on doing business abroad, guided by the principles of "green" logistics.